Analisis Inovasi Mak Cerdas Digital (MCD) dalam Perspektif Pemberdayaan Masyarakat di Kabupaten Nganjuk - Restu Gustiono; Bintoro Wardiyanto (SENTRI: Jurnal Riset Ilmiah, 2026)
This study examines the Mak Cerdas Digital (MCD) Program initiated by the Nganjuk Regency Communication and Informatics Office as a form of social innovation in empowering women, particularly housewives, through the use of digital technology. The study used a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation studies, and was analyzed using the Miles and Huberman model. The results show that MCD not only improves participants' technical skills in using social media and marketplaces but also encourages changes in self-confidence, mindset, and awareness of their potential as economic actors within the family. This program triggers the emergence of digital-based home businesses, expands marketing networks, and forms a mutually supportive learning community. However, there are still disparities in achievement among participants influenced by factors such as family support, device and internet access, and social barriers that still limit women's roles. These findings emphasize that digital empowerment requires a more comprehensive approach, encompassing not only technical but also social and cultural aspects. The MCD program has proven to be an effective local innovation model and has the potential to be replicated as a digital-based community empowerment strategy.